TINJAUAN PENILAIAN KINERJA KARYAWAN PADA PT POS INDONESIA (PERSERO) PULOGADUNG JAKARTA TIMUR - teni agus tina; Inggit Dessy Susanti; Eni Roma Wati; Vina Asiyah Zede (STIE Perbankan Indonesia, 2020)
Performance assessment on employees at government agencies needs to be improved, because in order to support a success inside government agencies .Every organization needs to know the development of its employees, in order to increase productivity of employees. Therefore, in a government agencies there needs to be performance assessment.Likewise, the PT Pos Indonesia where performance assessment is very important in order to achieve a goal that has been set. assessment of performance in PT Pos Indonesia is conducted quarterly to the work of employees.The purpose of the implementation of the employee performance is to know i e employee performance in working and assess the extent of the level of productivity employees pekerjaanya .The assessment on the post offices indonesia are carried out by employees concerned with specific his job or jobdesk masing-masing employees are how long do their job, and how the amount of work was finished on time. That way the employees concerned rated honesty but still supervised by superiors. The next performance appraisal is carried out by the Assistant Manager in the form of quality of work and level of employee attendance. In the assessment of Individual Performance Management System (ISMS) has several indicators into Aspects of Employee Performance Assessment include: attendance rate, quantity of work and quality of work.